TESTING FOR INDONESIAN AND VIET NAM PRICE TRANSMISSION IN THE UNITED STATES TUNA MARKETS - Wiranthi, Puspi Eko (Department of Economics, Faculty of Economics and Business, Universitas Brawijaya, 2021)
This study aims to analyze Indonesia and Viet Nam price transmission as the main exporters of frozen yellowfin tuna to the United States (US) assuming that the market structure is oligopoly. Using monthly time series data of Indonesia, Viet Nam and US frozen yellowfin tuna prices with harmonized system code 03034200 from January 2006 to December 2018 and analyzed through an Asymmetric Error Correction Model (AECM), this study finds that both prices of Indonesia and Viet Nam are integrated to the US prices. Additionally, there are two-way causality relationships between both exporting countries as well as Viet Nam and the US. The short-term price transmission of Viet Nam has an asymmetrical effect on Indonesian prices while on the long-term, the price transmission among three countries occurs symmetrically which indicates that a competitive international market exists. Indonesia’s policy in increasing its market share in the US is not independent, but it is influenced by the price of Viet Nam as its main competitor. The findings of this study are relevant to fill the gap in the literature by providing a supporting evidence regarding price transmission between two main exporters to the US frozen yellowfin tuna market.